1982
DOI: 10.1007/bf02372461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shading and powdery mildew infection on senescence of the root cortex and coleoptile of wheat and barley seedlings, and implications for root- and foot-rot fungi

Abstract: Summary Nuclear and cytoplasmic staining methods were used to study natural senescence of the root cortex and coleoptile of wheat and barley seedlings grown in glasshouse conditions. Coleoptiles of barley senesced more slowly than those of wheat, paralleling the known difference in rates of root cortex senescence in these cereals. The coleoptiles and root cortices of both cereals senesced more slowly in shaded than in unshaded conditions, but infection of the shoots of barley by Erysiphe graminis had little ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…RCS develops at the same rate in sterile and nonsterile conditions and is not enhanced by the presence of soil microorganisms or fungi (Henry and Deacon 1981;Lewis and Deacon 1982). However, RCS influences the size (Van Vuurde and Schippers 1980) and types Deacon and Lewis 1986) of rhizosphere bacterial and fungal populations, and regions of spring wheat roots that develop RCS support larger rhizosphere populations compared to regions with no RCS (Van Vuurde and Schippers 1980;Deacon and Lewis 1982;Deacon and Lewis 1986).…”
Section: Regulation Of Rcs Developmentmentioning
confidence: 99%
“…RCS develops at the same rate in sterile and nonsterile conditions and is not enhanced by the presence of soil microorganisms or fungi (Henry and Deacon 1981;Lewis and Deacon 1982). However, RCS influences the size (Van Vuurde and Schippers 1980) and types Deacon and Lewis 1986) of rhizosphere bacterial and fungal populations, and regions of spring wheat roots that develop RCS support larger rhizosphere populations compared to regions with no RCS (Van Vuurde and Schippers 1980;Deacon and Lewis 1982;Deacon and Lewis 1986).…”
Section: Regulation Of Rcs Developmentmentioning
confidence: 99%
“…Because shading reduced the total amounts of assimilates, it was expected to enhance root PCD; on the contrary, the root PCD was significantly reduced. This result could be reconciled with the hypothesis if it was assumed that shading reduced competition for assimilates within the root system, and if this reduced competition more than offset the reduction in total assimilate supply to the roots (Lewis and Deacon 1982). Another possible reason was that shading could reduce assimilation of the whole plant, so root PCD which was beneficial for nutrients remobilization was reduced.…”
Section: Discussionmentioning
confidence: 72%
“…The enhanced root PCD in LC might be an adaptive reaction of roots to assimilate shortage. However, Lewis and Deacon (1982) reported that root PCD was significantly reduced by shading (green plastic netting placed around the plant containers and between them and the light). Because shading reduced the total amounts of assimilates, it was expected to enhance root PCD; on the contrary, the root PCD was significantly reduced.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Deficiencies of nitrogen, and to term first introduced by Henry & Deacon (1981) to a lesser extent phosphorus and potassium, were also describe the progressive death of cells inwards from shown by GiUespie & Deacon (1988) to increase the the epidermis toward the stele of cereal and grass number of anucleate cortical cells in whole and roots with age A general pattern of cortical cell excised seminal root pieces of wheat, death was also described, and later found to be Deficiencies of mobile nutrients such as nitrogen, consistent for wheat barley, oats and rye, although phosphorus and potassium accelerate the senescence the rate differs between the species (Henry & of leaves on the shoot (Addicott & Lyon, 1973) due Deacon 1981-Lewis & Deacon, 1982 to the net withdrawal of mineral nutrients. If root Mitchell 1985• Yeates & Parker, 1986.…”
mentioning
confidence: 99%